2023
DOI: 10.2169/internalmedicine.9607-22
|View full text |Cite
|
Sign up to set email alerts
|

A Woman with Rheumatoid Arthritis Who Successfully Delivered a Healthy Child with Continuous Administration of Sarilumab Throughout Pregnancy

Abstract: We herein report a patient with rheumatoid arthritis (RA) who successfully delivered a healthy child with continuous administration of sarilumab throughout pregnancy. She delivered her first child, a healthy boy, following in vitro fertilization-embryo transfer (IVF-ET) while using etanercept and low-dose prednisolone. Disease activity persisted after delivery, so etanercept was switched to sarilumab. She became pregnant by IVF-ET again. Because RA was still active, sarilumab was continued during pregnancy. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Generally, studies have not found evidence to support significant immunosuppression by TNFα inhibitors since there is no observed increase in infection rates in exposed infants, regardless of whether exposure occurred early or late in pregnancy [22 ▪▪ ,24]. Overall, the recommendation from rheumatologic societies is to continue TNFα inhibitors throughout pregnancy and transiently hold them during the third trimester, if the underlying disease is well controlled [22 ▪▪ ,25,29,30,38,39,40 ▪ ,41,42,43 ▪ ,44] (Table 2).…”
Section: Potential To the Fetus And Newborn Due To Biologics Usementioning
confidence: 99%
“…Generally, studies have not found evidence to support significant immunosuppression by TNFα inhibitors since there is no observed increase in infection rates in exposed infants, regardless of whether exposure occurred early or late in pregnancy [22 ▪▪ ,24]. Overall, the recommendation from rheumatologic societies is to continue TNFα inhibitors throughout pregnancy and transiently hold them during the third trimester, if the underlying disease is well controlled [22 ▪▪ ,25,29,30,38,39,40 ▪ ,41,42,43 ▪ ,44] (Table 2).…”
Section: Potential To the Fetus And Newborn Due To Biologics Usementioning
confidence: 99%